Party branches, policy perception and corporate social responsibility: Evidence from Chinese private enterprises - Yao, Zhenjiu; Zhang, Zengtian; Ma, Jun (Frontiers in Psychology, 2023)
Introduction Party branches embedded in private enterprises are a unique phenomenon in the Chinese economy, but few studies have focused on the economic consequences. We hope to explore the impact of party branches on small and medium-sized private enterprises’ corporate social responsibility (CSR) in China in order to fill the gaps in current research. Methods Data were used from the 11th Chinese Private Enterprise Survey (CPES) in 2014. The study uses the methodology of fixed effect model, mediation analysis and moderation analysis. Moreover, propensity score matching and Heckman two-step method deal with the endogeneity problem and check the robustness of the results. Results We find that, first, the embedding of party branches will improve the CSR performance of private enterprises in various dimensions by enhancing the perception of private enterprises in policy; second, in various influence pathways, the party branches will enhance the perceptions of policy related to economic interests, which has a more significant impact on enhancing the performance of philanthropic CSR. Further research reveals that business owners’ first-given and later-generated political connections support the party branches’ perception of policies related to economic and social interests, respectively. Discussion The findings suggest that political intervention by China’s ruling party in private firms promotes CSR performance, but this is influenced by the political connections of the firm owners. In addition to providing empirical support for the study of corporate behavior in the Chinese context, this paper identifies the impact and development trajectory of the party branches of China’s ruling party on CSR. However, this paper does not discuss the implicit costs required for party branches to promote CSR, and we hope that future research will make further explorations.